Geographical space and service use in agriculture: The view from the perspective of multilayer networks - Kovács, László; Szőke, Viktória (Hungarian Geographical Bulletin, 2025)
Location theory has shown that the location of businesses follows specific patterns: primarily, the site of production, transportation costs, markets, and workforce are considered the main factors influencing business location. However, less research focuses on the spatial distribution of service use of actual businesses. Based on empirical data collected in the Hungarian counties Vas and Zala, the paper shows how the service use of agricultural producers is distributed in space. Using a questionnaire, we show that services are primarily used in nearby towns, although in some exceptional cases, small villages can also function as service providers to agribusinesses. Based on the results, we argue that agricultural producers’ business connections are best described as multilayer networks in which layers are interconnected. We assume, based on a shift towards more intensive service use of agricultural producers due to the advances in agriculture 4.0, that on these layers, physical roads will maintain their importance; parallel, however, the weight of digital connections will increase.